Convict criminology: voices from prison - Richards, Stephen C. (Race, ethnicity, 2008)
Today, more than two million men and women reside in our nation’s jails and prisons. This population is disproportionately black and brown, while those who attend universities are nearly exclusively white. The drug war has devastated minority communities and has contributed to a dramatic increase in the rate of incarceration for people of color (Miller, 1996; Austin et al., 2001). In this article, we discuss the following topics: convict criminology perspective, inviting convicts to college programs, convicts as “invisible” minorities, minorities in prisons, and correctional education and recidivism. The Convict Criminology course is taught at one university and two state prisons. A ten-question survey was administered to the three classes. The respondents’ replies are provided as a means for comparing university and convict students’ perceptions and thoughts about the course they completed. As simply as possible, we have outlined one way that universities can help prisoners to exit prison and enter college